Development of a self propelled pre - germinated paddy seeder - BRIJESH KUMAR R GANGA NIMMY JOSE CHERIPURAM; Er. Manoj Mathew (Guide) (Tavanur 2001 Kelappaji College of Agricultural Engineering and Technology)
to study the metering characteristics of drums for pre-germinated seeds and to conduct field testing of self-propelled paddy seeder.
Development of a self propelled pre - germinated paddy seeder